1)z^2=z拔(2)z^2+|z|=0
举一反三
- z=0为f(z)=z^2 (e^(z^2 )-1)的 级零点,
- 设方程\(z^2+y^2+z^2 = 4z\)确定函数\(z=z(x,y)\),则\( { { {\partial ^2}z} \over {\partial {x^2}}} =\) A: \( { { { { (2 - z)}^2} + {x^2}} \over { { {(2+ z)}^3}}}\) B: \( { { { { (2 - z)}^2} + {x^2}} \over { { {(2 - z)}^3}}}\) C: \( { { { { (2 - z)}^2} -{x^2}} \over { { {(2 - z)}^3}}}\) D: \( { { { { (2 + z)}^2} + {x^2}} \over { { {(2 - z)}^3}}}\)
- 【简答题】设 z 1 =4 + 3i , z 2 =2 - 3i ,计算 z 1 · z 2
- 若检验的假设为H0∶μ=μ0,H1∶μ≠μ0,则拒绝域为 ( )。 A: z >; zα B: z <; zα C: z >; zα/2或z <; -zα/2 D: z >; zα或z <; -zα
- 若复数z 1=1+i ,z 2=3-i ,则z 1·z 2等于